ANALISIS ANALISIS PENGARUH ONLINE CUSTOMER REVIEW, DISKON, DAN GRATIS ONGKIR TERHADAP KEPUTUSAN PEMBELIAN DI MARKETPLACE SHOPEE DI WILAYAH SOLO RAYA: ONLINE CUSTOMER REVIEW, DISKON, DAN GRATIS ONGKIR - Anjani Rahmawati (JURNAL WIRANOMIKA, 2025)
The purpose of this study was to determine the effect of online customer reviews, discounts, and free shipping on purchasing decisions for Shopee users in Solo Raya. There were 96 respondents collected for this study using purposive sampling technique, quantitative research method with certain requirements. Using a Likert scale with data collection through a questionnaire. Instrument test, classical assumption test, multiple linear regression analysis, and hypothesis testing are some of the data tests used in this study. It can be concluded from the t test results that online customer reviews, discounts, and free shipping have an effect on purchasing decisions for Shopee users in Solo Raya.